USE OF LEAN METHODOLOGY IN A RESIDENTIAL BUILDING CONSTRUCTION COMPANY IN BELO HORIZONTE: : A CASE STUDY (REMUNOM, 2025)
Civil construction plays a strategic role in Brazil's socioeconomic development. However, the sector faces challenges such as low productivity, lack of standardisation, and high labour turnover. This article investigates the application of the Lean Construction methodology in a large-scale residential project, focusing on timeline optimisation and process improvement. The research employs a case study approach, comparing blocks constructed with and without Lean principles, incorporating tools such as Value Stream Mapping, Scrum, and Obeya. Results indicate that despite cultural and logistical challenges, Lean implementation reduced the average lead time by 32%, highlighting its potential to enhance efficiency and reduce costs. Nonetheless, barriers such as resistance to change and the complexity of the supply chain underscore the need for robust planning and continuous team engagement. This study underscores the value of Lean Construction for Brazil’s construction industry, offering practical insights into the application of this methodology in a local context.